Intranasal immunization with heat shock protein 60 induces CD4+CD25+GARP+ and type 1 regulatory T cells and inhibits early atherosclerosis. (24th November 2015) - Zhong, Y; Tang, H; Wang, X; Zeng, Q; Liu, Y; Zhao, Xi; Yu, K; Shi, H; Zhu, R; Mao, X
Summary: Atherosclerosis is an autoimmune inflammatory disease involving both innate and adaptive immune mechanisms. Immune tolerance induction may have therapeutic potential for the suppression of atherosclerosis. Current interest is directed towards mucosal tolerance induction, especially nasal tolerance. Previous studies have shown that heat shock protein 60 (HSP60) is recognized as an important autoantigen in atherosclerosis, and nasal or oral HSP60 can induce tolerance and ameliorate atherosclerosis by inducing several subsets of regulatory T cells (Tregs ) such as latency-associated peptide (LAP) + and forkhead box transcription factor 3 (FoxP3) + Tregs . However, little is known regarding the detailed mechanisms of nasal tolerance. Here, we again investigated the impact of nasal HSP60 on atherosclerosis and the mechanisms underlying the anti-atherosclerosis responses. We found that nasal HSP60 caused a significant 33·6% reduction in plaque size at the aortic root in the early stages of atherosclerosis ( P  < 0·001). Notably, a significant increase in activated CD4 + CD25 + glycoprotein A repetitions predominant (GARP) + Tregs, type 1 Tregs (Tr1 cells), and CD4 + CD25 + FoxP3 + Tregs, as well as a marked decrease in the numbers of type 1 and 17 T helper cells was detected in the spleens and cervical lymph nodes of HSP60-treated mice. Moreover, nasal HSP60 increases the production of transforming growth factor (TGF)-β and interleukin (IL)-10 and decreases the secretion of IFN-γ and IL-17. Interestingly, the atheroprotective role of nasal HSP60 treatment was abrogated partly by the neutralization of IL-10. Our findings show that nasal administration of HSP60 can attenuate atherosclerotic formation by inducing GARP + Tregs, Tr1 cells and FoxP3 + Tregs, and that these Tregs maintain immune homeostasis by secreting IL-10 and TGF-β.